1990
DOI: 10.1042/bj2700397
|View full text |Cite
|
Sign up to set email alerts
|

Insulin responsiveness in skeletal muscle is determined by glucose transporter (Glut4) protein level

Abstract: Glucose transport in skeletal muscle is mediated by two distinct transporter isoforms, designated muscle/adipose glucose transporter (Glut4) and erythrocyte/HepG2/brain glucose transporter (Glut1), which differ in both abundance and membrane distribution. The present study was designed to investigate whether differences in insulin responsiveness of red and white muscle might be due to differential expression of the glucose transporter isoforms. Glucose transport, as well as Glut1 and Glut4 protein and mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
3
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(165 citation statements)
references
References 22 publications
14
142
3
6
Order By: Relevance
“…24,31 In the present investigation, we found that chronic antagonism of Ang II receptors caused small (15% to 22%) but significant increases in GLUT-4 protein expression in both oxidative (soleus) and substantially glycolytic (plantaris) skeletal muscle and in the highly oxidative myocardium (Figure 7). At least in the soleus muscle, this increase in GLUT-4 protein could have contributed to enhancement of insulin action on glucose transport after chronic irbesartan treatment.…”
Section: Discussionmentioning
confidence: 76%
“…24,31 In the present investigation, we found that chronic antagonism of Ang II receptors caused small (15% to 22%) but significant increases in GLUT-4 protein expression in both oxidative (soleus) and substantially glycolytic (plantaris) skeletal muscle and in the highly oxidative myocardium (Figure 7). At least in the soleus muscle, this increase in GLUT-4 protein could have contributed to enhancement of insulin action on glucose transport after chronic irbesartan treatment.…”
Section: Discussionmentioning
confidence: 76%
“…Bovine and fetal bovine sera were purchased from HyClone, Logan, Utah. All radiolabeled compounds were obtained from New England Nuclear, Boston, Mass., or ICN Biomedicals Inc., Irvine, Calif. GLUT1 and GLUT4 antibodies were prepared and characterized as previously described (22). The 3T3-L1 cells used in these experiments were obtained from Howard Green, Harvard University, Boston, Mass.…”
Section: Methodsmentioning
confidence: 99%
“…Translocation of intracellular vesicles containing the insulinresponsive glucose transporter Glut4 to the cell surface is one of the most important effects of insulin in adipose and skeletal muscle tissues (1)(2)(3)(4). In the absence of insulin, approximately 95% of cellular Glut4 is sequestered in an intracellular compartment.…”
mentioning
confidence: 99%